2014
DOI: 10.1021/bi5004475
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural and Pharmacological Characterization of α-Elapitoxin-Dpp2d, an Amidated Three Finger Toxin from Black Mamba Venom

Abstract: We isolated a novel, atypical long-chain three-finger toxin (TFT), α-elapitoxin-Dpp2d (α-EPTX-Dpp2d), from black mamba (Dendroaspis polylepis polylepis) venom. Proteolytic digestion with trypsin and V8 protease, together with MS/MS de novo sequencing, indicated that the mature toxin has an amidated C-terminal arginine, a posttranslational modification rarely observed for snake TFTs. α-EPTX-Dpp2d was found to potently inhibit α7 neuronal nicotinic acetylcholine receptors (nAChR; IC₅₀, 58 ± 24 nM) and muscle-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…Proteomic characterization of the venom has revealed 41 different proteins and one nucleoside [ 4 ]. Major proteins reported include dendrotoxins, α-neurotoxins, muscarinic toxins, fasciculins, calciseptine, mamba intestinal toxins, and mambalgin [ 4 , 19 , 20 , 21 , 22 , 23 ]. Minor proteins include metalloproteinases, hyaluronidase, prokinecitin, nerve growth factor, phospholipase A 2 , 5’-nucleotidase, and phosphodiesterase [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic characterization of the venom has revealed 41 different proteins and one nucleoside [ 4 ]. Major proteins reported include dendrotoxins, α-neurotoxins, muscarinic toxins, fasciculins, calciseptine, mamba intestinal toxins, and mambalgin [ 4 , 19 , 20 , 21 , 22 , 23 ]. Minor proteins include metalloproteinases, hyaluronidase, prokinecitin, nerve growth factor, phospholipase A 2 , 5’-nucleotidase, and phosphodiesterase [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dendrotoxins primarily act on the voltage-dependent potassium channels where they potentiate effects of acetylcholine by facilitating its release at pre-synaptic nerve terminals, thereby eliciting excitatory effects [ 11 , 24 , 25 ]. α-Neurotoxins bind to the nicotinic cholinergic receptors at the motor end-plates of muscle fibers and have the capacity to cause flaccid paralysis that leads to labored breathing and death [ 19 ]. Muscarinic toxins bind to muscarinic cholinergic receptors [ 26 ], and fasciculins inhibit anticholinesterase; thus, there is an increase in the levels of acetylcholine at neuromuscular junctions, which manifests as generalized, long-lasting fasciculations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This post-translational modification is rarely observed for snake venom three-finger toxins. Assay binding studies showed that α-elapitoxin strongly inhibits α 7 nAChR; however, it was suggested that the C-terminal modification does not significantly affect toxin selectivity [ 73 ]. The three-finger toxin peptides have served as an excellent molecular probe in deciphering the structural and functional details of nAChR since the discovery of the iconic peptide α-bungarotoxin from the venom of a krait, Bungarus multicinctus [ 74 , 75 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…Structure built upon35; (G,H) Alfa-elapitoxin-Dpp2c (P01397) from D. polylepis as an example of a type 2 α-neurotoxin. Structure built upon56. (A,C,E,G) Residues coloured according to alanine substitution effect in log 2 fold-change, where magenta indicates that a residue is of particular importance for antibody recognition.…”
Section: Figurementioning
confidence: 99%